Cuscuta Chinensis potentiate the effect of methotrexate in Rheumatoid Arthritis Induced Rats. - Ahmed Shawqy Saadoon; Mustafa Ghazi Alabbassi; Nadia Hameed Mohammed (College of Pharmacy / Mustansiriyah University, 2022)
Background Rheumatoid arthritis (RA) is a chronic destructive inflammatory disease related to a breakdown in immune tolerance. This disease is characterized by joint inflammation, swelling, and in severe cases deformation may occur. Cuscuta Chinensis (C. Chinensis) is a parasitic plant, grow around other plants to absorb nutrient and water from them. C. Chinensis has a wide range of chemicals that produce a wide range of pharmacological activates. Because of its anti-oxidant and anti-inflammatory effect, it was considered as a good candidate to assess its role in RA. Methods: Rheumatoid arthritis was induced by injection of Complete Freund's Adjuvant inside the foot-pad of male albino rats. The animals were grouped in four groups as follows group 1 considered as a normal control group, group 2 consider as positive control arthritis, group 3 treated with methotrexate (MTX), group 4 treated with MTX and C. Chinensis extract. On day 14 of immunization, treatments began and last for 21 days, at the end of the experiment all animals were sacrificed and serum was collected. The serum markers that had been evaluated were MMP3, VEGF, and SOD. Throughout the experiment time the body weight was evaluated. Results The combination significantly (P-value ≤ 0.05) improves objective parameter of RA which was the body weight. Also significantly decrease (P-value ≤ 0.05) the serum level of MMP3, VEGF, and considerably increase serum SOD. Conclusion: The combination has a significant beneficial role in suppression of destructive enzyme (MMP3), angiogenic stimulators (VEGF), and increase serum SOD enzyme.